2019
DOI: 10.1017/s174455231900003x
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse and parenting: making drugs and gender in the family court

Abstract: Children tend to be represented as the quintessential victims of the ‘drug problem’, with drug-using parents, particularly mothers, characterised as vectors of the risks posed. Although evidence of drug use is not per se an impediment to retaining care of, or contact with, children (per Lady Hale in Re B [2013] UKSC 33, at para. 143), it does pose one of the greatest challenges to social and political norms about ‘good parenting’, and often has a powerful impact on decisions about care within UK family courts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Being female or non‐binary, Aboriginal or Torres Strait Islander, experiencing assault and having a higher number of children was associated with greater odds of having a child removed into out‐of‐home care. Our results are consistent with previous studies in which maternal substance use features more heavily in child protection involvement than paternal substance use [41]. Further explorations of interactions by gender indicated that incarceration was associated with a higher risk of child placement into OOHC for women compared to men, while treatment on OAT was more protective for women than for men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Being female or non‐binary, Aboriginal or Torres Strait Islander, experiencing assault and having a higher number of children was associated with greater odds of having a child removed into out‐of‐home care. Our results are consistent with previous studies in which maternal substance use features more heavily in child protection involvement than paternal substance use [41]. Further explorations of interactions by gender indicated that incarceration was associated with a higher risk of child placement into OOHC for women compared to men, while treatment on OAT was more protective for women than for men.…”
Section: Discussionsupporting
confidence: 91%
“…Further explorations of interactions by gender indicated that incarceration was associated with a higher risk of child placement into OOHC for women compared to men, while treatment on OAT was more protective for women than for men. These differing associations by gender may reflect the higher likelihood for mothers to be a child's main carer; however, they may also relate to increased scrutiny faced by women based on social and political norms and expectations about parental roles [41,42]. Surveys of community attitudes indicate high levels of stigma towards mothers who use illicit drugs, with one-third of participants in a US survey reporting a belief that a mother who is receiving treatment for their opioid use disorder during pregnancy should be arrested, while two-thirds felt that the infant should be removed from their care [35,43].…”
Section: Discussionmentioning
confidence: 99%
“…This increased scrutiny on women has been linked to ‘mother blaming’ in professional responses to DVA (Humphreys & Absler, 2011) and can similarly be evidenced in relation to PSM. Conceptualizations of good ‘motherhood’ do not include substance misuse (Flacks, 2019), and the stigma and shame surrounding these issues (as well as fears of their children being removed from their care) can act as a significant barrier for mothers wanting to engage with services (Neale, Tompkins, Marshall, Treloar, & Strang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have addressed how PSU affects children, and some have engaged with the problematisation of PSU in policy and legal discourses (Flacks, 2019a(Flacks, , 2019bWhittaker et al, 2020), research on the interpretation and constitution of PSU by family court actors is lacking. This paper is based on interviews with social workers, solicitors, barristers, psychiatrists, and district judges, with the aim of exploring how participants understood the relationship between parental AOD use and child protection.…”
Section: Introductionmentioning
confidence: 99%